THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE, TRANSACTIONAL AND JOB SATISFACTION ON THE PERFORMANCE OF TEACHERS OF SMA NEGERI 1 MAKMUR - Arifin, A Hadi; Marbawi, Marbawi; Heikal, Mohd; Afrina, Mutia (RADJA PUBLIKA, 2022)
This study aims to determine the effect of transformational leadership style, transactional leadership style and job satisfaction on the performance of SMA Negeri 1 Makmur teachers. This study uses primary data obtained by distributing questionnaires to 39 respondents. This study uses a quantitative and qualitative approach. The data analysis method used is multiple linear regression model with the help of SPSS. The results showed; Transformational leadership style has a negative and insignificant effect on teacher performance, while transactional leadership style and job satisfaction has a positive and significant effect on teacher performance.